Autophagy, apoptosis, and inflammation response of Sebastiscus marmoratus to different concentrations of hydroxychloroquine - Liu, Yifan; Luo, Jun; Ren, Chuanchen; Chen, Long; Zhao, Yifeng; Yin, Xiaolong; Liu, Bingjian (Frontiers in Marine Science, 2024)
Hydroxychloroquine (HCQ) is an important public health therapeutic agent widely used in the prevention and treatment of malaria and autoimmune diseases, with some antiviral effects, as well as a common autophagy inhibitor. Its autophagy-inhibiting effect attracts great research interest in mammals but is still little studied in fish. We even have no idea about the effects of HCQ on different tissues of fish and what concentrations should be used for safety studies. This study investigated the effect of different concentration of HCQ treatments on the survival, tissue structure, and expressions of genes related to autophagy, apoptosis, and inflammation in the gill, spleen, testis, and ovary of Sebastiscus marmoratus. The results showed that the higher HCQ concentration (77.40 and 154.80 mg/mL) led to mass mortality within an hour.The half-lethal concentration (LC50, 24 h) of HCQ for S. marmoratus was approximately 48.95 mg/mL. When exposed to 30.96 mg/mL HCQ for 24 hours, autophagy was blocked as revealed by electron microscopy from gill, spleen and testis of fish. The expressions of autophagy-related genes (LC3/Cx43), apoptosis-related genes (Cas3/p53), and inflammation-related genes (TNF-α/IL8) exhibited tissuespecific and dose-dependent responses. The gonads showed preferential expression of all these genes and were found to be sensitive and regular after HCQ treatment. For example, at a concentration of 30.96 mg/mL, the testis demonstrated a regularity that suggests it is an ideal candidate tissue for studying the role of HCQ or autophagy. This study systematically revealed the response of S. marmoratus to different concentrations 3 of HCQ and provided optional assay concentrations for key tissues, serving as an important reference for the future studies on HCQ and autophagy in S. marmoratus.Furthermore, the potential crosstalk between autophagy, apoptosis, and inflammatory pathways initially identified in this study could be helpful for the future research on autophagy regulation in marine fish.